2017
DOI: 10.21037/tp.2017.10.02
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic syndrome in children and adolescents

Abstract: Prevalence of metabolic syndrome in children and adolescents is increasing, in parallel with the increasing trends in obesity rates. Varying definitions of this syndrome have hindered the development of a consensus for the diagnostic criteria in the pediatric population. While pathogenesis of metabolic syndrome is not completely understood, insulin resistance and subsequent inflammation are thought to be among its main mechanistic underpinnings. Overweight and obesity are cardinal features, along with abnormal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
141
2
8

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 190 publications
(183 citation statements)
references
References 81 publications
7
141
2
8
Order By: Relevance
“…The prevalence of MetS is also considerably higher than a meta analysis ndings done in chinese children and adolescents, where 1.8% (IDF) and 2.6% (ATP III) were found to have MetS [135]. This implies that MetS is increasing throughout the world, including in LMICs and it is supported by the previous reviews [14,136,137].…”
Section: Discussionmentioning
confidence: 52%
“…The prevalence of MetS is also considerably higher than a meta analysis ndings done in chinese children and adolescents, where 1.8% (IDF) and 2.6% (ATP III) were found to have MetS [135]. This implies that MetS is increasing throughout the world, including in LMICs and it is supported by the previous reviews [14,136,137].…”
Section: Discussionmentioning
confidence: 52%
“…This demonstrates that patients with PKU and excess weight are substantially more susceptible to developing disorders associated with metabolic syndrome. [36][37][38][39][40] The present review identified a frequency of overweight ranging from 7.8 to 32.6% in studies including children and adolescents with PKU. This prevalence was lower than that previously found by White and Acosta, 11 considering that 68.5% of the evaluated children presented the outcome.…”
Section: Indicators Analyzedmentioning
confidence: 99%
“…Lifshitz estimated that 75% to 80% of adolescents with obesity will maintain or increase their level of obesity in adulthood . Rising rates of obesity in children have been accompanied by increasing rates of metabolic syndrome . Despite these prominent associations, little is known about how excess weight relates to body composition measures such as fat mass (FM) in children outside of population‐level estimates.…”
Section: Introductionmentioning
confidence: 99%